2018
DOI: 10.1155/2018/1948261
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bilateral Transversus Abdominis Plane and Ilioinguinal-Iliohypogastric Nerve Blocks for Postcaesarean Delivery Pain Relief under Spinal Anesthesia

Abstract: Background Caesarean delivery can be associated with considerable postoperative pain. While the benefits of transversus abdominis plane (TAP) and ilioinguinal-iliohypogastric (II-IH) nerve blocks on pain after caesarean delivery via Pfannenstiel incision have been demonstrated, no enough investigations on the comparison of these blocks on pain after caesarean delivery have been conducted in our setup. Method An institutional-based prospective observational cohort study was conducted to compare the analgesic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
(32 reference statements)
1
10
0
2
Order By: Relevance
“…Study design (non-randomized, retrospective), the use of intrathecal morphine & blocks done with ultrasound guided technique could have contributed for the difference seen to our nding [18]. Similarly a cohort by Seid et al, in a study done in Gondar, Ethiopia found that 24 hour total tramadol consumption was lower in II/IH group compared to TAP group (P = 0.009) [19]. Difference in study design and different people performing the blocks in their cohort could explain this discrepancy.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Study design (non-randomized, retrospective), the use of intrathecal morphine & blocks done with ultrasound guided technique could have contributed for the difference seen to our nding [18]. Similarly a cohort by Seid et al, in a study done in Gondar, Ethiopia found that 24 hour total tramadol consumption was lower in II/IH group compared to TAP group (P = 0.009) [19]. Difference in study design and different people performing the blocks in their cohort could explain this discrepancy.…”
Section: Discussionmentioning
confidence: 70%
“…However, at 36 & 48 hour intervals was pain scores were lower in TAP compared to II/IH group both at rest & on purposeful movement (p < 0.0005). Seid et al, Anatoli Stav, et al & So ene Ben Marzouk et al found no difference in NRS score between groups both at rest and on movement during their 24 hour follow up for post cesarean section pain (P > 0.05) [19,24,25]. Our result is also supported by a study comparing TAP with IINB + wound in ltration for post-operative analgesia after inguinal surgery in adults, did not found signi cant difference in pain score between groups (P > 0.05) [26].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Selain itu, efek samping terkait opioid ini dapat menghasilkan masalah lain untuk ibu yang baru melahirkan seperti keterlambatan inisiasi menyusui dini dan gangguan ikatan ibu/bayi. 4 Saat ini banyak cara yang paling aman dan efektif dari intervensi untuk manajemen nyeri pasca operasi caesar seperti anestesi lokal dengan infiltrasi kulit, analgesia epidural, dan blok bidang seperti tranversus abdominis plane (TAP) dan ilioinguinal-iliohypogastric (II-IH). 4 Oleh sebab itu perlu diketahui keefektivan dari blok TAP sebagai salah satu rejimen manajemen nyeri pasca operasi caesar.…”
Section: Pendahuluanunclassified
“…Controversy still exists regarding the analgesic efficacy of transverse abdominis plane (TAP) block versus ilioinguinal or iliohypogastric (IL/IH) nerve block for postoperative pain management following cesarean section [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%